2012
DOI: 10.1128/aem.01232-12
|View full text |Cite
|
Sign up to set email alerts
|

Specificity of Associations between Bacteria and the Coral Pocillopora meandrina during Early Development

Abstract: cRelationships between corals and specific bacterial associates are thought to play an important role in coral health. In this study, the specificity of bacteria associating with the coral Pocillopora meandrina was investigated by exposing coral embryos to various strains of cultured marine bacteria, sterile seawater, or raw seawater and examining the identity, density, and location of incorporated cells. The isolates utilized in this experiment included members of the Roseobacter and SAR11 clades of the Alpha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
57
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(61 citation statements)
references
References 65 publications
3
57
0
Order By: Relevance
“…A number of recent studies provide corroborative evidence that Roseobacter is a dominant bacterial group in very early developmental stages of corals (Apprill et al . , ; Sharp et al . ; Ceh et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of recent studies provide corroborative evidence that Roseobacter is a dominant bacterial group in very early developmental stages of corals (Apprill et al . , ; Sharp et al . ; Ceh et al .…”
Section: Discussionmentioning
confidence: 99%
“…In the broadcast‐spawning species Pocillopora meandrina, the absence of bacteria in oocytes and newly released larvae, but presence in 1‐week‐old larvae, suggests that horizontal transmission may occur in spawning species (Apprill et al . , ). The pattern emerging from this limited number of studies is consistent with transmission mode of bacterial communities being determined by reproductive mode (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Recent efforts to describe the dynamics and structure of larval–microbiome interactions have suggested that this microbial community is specific to the larval host species while remaining distinct from the environmental metagenome (Apprill et al, ; Galac, Bosch, & Janies, ; Lema et al, ; Mortzfeld et al., ). These patterns are consistent with other taxa and their developmental stages (Gilbert, ; Gilbert, Bosch, & Ledón‐Rettig, ; McFall‐Ngai, ; McFall‐Ngai & Ruby, ; Rosenberg & Zilber‐Rosenberg, ; Schwab et al, ; Walker & Lesser, ).…”
Section: Oceanography and Larval Evolutionmentioning
confidence: 99%
“…As is the case for Roseobacter interactions with other eukaryotes, it is not yet clear whether a physical association signifies a specific mutualistic interaction. There is evidence that roseobac-ters may play a role in coral reproduction, based on both consistent associations between the bacteria and early developmental stages of corals (112,113) as well as increases in Roseobacter abundance after coral mass spawning (114). Roseobacters may also have a role in coral bleaching by acting as probiotics against pathogens (115, 116).…”
Section: Roseobacter-coral Interactionsmentioning
confidence: 99%